C1q rs292001 polymorphism and C1q antibodies in juvenile lupus and their relation to lupus nephritis. (28th July 2015) - Mosaad, Y. M.; Hammad, A.; Fawzy, Z.; El‐Refaaey, A.; Tawhid, Z.; Hammad, E. M.; Youssef, L. F.; ElAttar, E. A. A.; Radwan, D. F.; Fawzy, I. M.
Summary C1q deficiency is related strongly to systemic lupus erythematosus (SLE), but very few and inconsistent studies explored the single nucleotide polymorphisms of the C1q gene in relation to juvenile SLE (jSLE) and lupus nephritis (LN). The objective of this study was to analyse whether C1q rs 292001 polymorphism is associated with SLE and disease phenotype, especially nephritis, and to investigate the relation between this polymorphism and clinical data, treatment outcome, serum level of C1q protein and antibodies. Typing of C1q rs292001 polymorphism using restriction fragment length polymorphism and measuring serum levels of C1q protein and antibodies by enzyme‐linked immunosorbent assay (ELISA) were performed for 130 children with SLE and 208 healthy controls. The A allele of C1q rs292001 was associated with jSLE and LN (P = 0·005 and 0·013, respectively) and the AA genotype was associated with jSLE (P = 0·036). Low serum levels of C1q protein were found in jSLE and LN (P < 0·001 and 0·009, respectively), and these levels were increased after treatment in patients with LN (P = 0·009) and active renal disease (P = 0·027). Higher titres of C1q antibodies were found in patients with LN (P = 0·015) and correlated negatively with C1q protein level (P < 0·001) and patient age (P = 0·04). The A allele and AA genotype of C1q rs292001 can be considered a susceptibility risk factor and the GG genotype could be considered protective for jSLE and LN in the studied cohort of Egyptian children. Decreased serum levels of C1q protein and increased titres of C1q antibodies may be involved in the pathogenesis of jSLE, especially LN.